Anthropometric and Physiological Criteria in Selection of Team National Football U17 - Kuriu, Avdyl; Shehu, Aida (Arena-Journal of Physical Activities, 2019)
The purpose of the study to explore the main medical-sport data for the selection of national team players U 17. There are many factors important in determining the success of a soccer player. Soccer players have to adapt to the physical and physiological demands of the soccer game. Players may not need to have an extraordinary capacity within any of the areas of physical performance but must possess a reasonably high level within all areas. Methods. In this research are included 35 players who did not pass the age of 17 years. The searches were conducted in the sports lab certified in March 2018, the NSC. Footballers do complete blood and urine tests. For the study effect we have evaluated some data: hemoglobin, age, height, weight, percentage fat, aerobic power absolute and relative values. S A was realized using software, IBM SPSS 20. Results. In this research the height is 175,129 ± 5,679 which indicates that the demand for high stature players continues. Weight, mass index and fat percentage show that players are in regular football body composition. Absolute aerobic power 2,546 ± 0,370 and relative 40,054 ± 5,644 indicates that this physical fitness for age is lowered. The hemoglobin average in our values is 12, 23 ± 0.869, which is below normal sports limits. Conclusions. Selection of players at the elite level needs some specialist from various fields in sports, where in addition to external visibility, sportsman should be evaluated by functional and psychological side.